The Trend of ‘Cyber Technology Ethical’, 1996-2021 in Elementary School: Bibliometric Approach - Elihami, Elihami (Universitas Pahlawan Tuanku Tambusai, 2022)
Transformation of research on cyber character education regarding Islamic education from 1996 to 2021. The purpose of this research is to find out the implementation of character education for students, especially in elementary schools and analyze the trend of publication of Islamic education in elementary schools in the 21st century era . The research method used is qualitative research using VOSviewer application analysis in bibliographic reviews taken from the most productive authors, journals, keywords, and citation references analyzed from 1996-2021. The information was obtained from the Google Scholar Science Citation Index database. Qualitative methodology was used in the investigation using the Vosviewer and Nvivo plus 12 applications. The results of the research on the cyber trend of education show that character education is still far from expectations towards society 5.0. The conclusion of the research illustrates that students must be made a top priority in welcoming the industrial era as the nation's next generation, especially among elementary schools. The implication is that there is a contribution in the latest innovation model that cannot be separated from the role model of education that is virtuous and integrated in the future era.